Neomorphic effects of the neonatal anemia (Nan-Eklf) mutation contribute to deficits throughout development - Planutis, Antanas (Development, 2017)
Transcription factor control of cell-specific downstream targets can be significantly altered when the controlling factor is mutated. We show that the semi-dominant neonatal anemia (Nan) mutation in the EKLF/KLF1 transcription factor leads to ectopic expression of proteins that are not normally expressed in the red blood cell, leading to systemic effects that exacerbate the intrinsic anemia in the adult and alter correct development in the early embryo. Even when expressed as a heterozygote, the Nan-EKLF protein accomplishes this by direct binding and aberrant activation of genes encoding secreted factors that exert a negative effect on erythropoiesis and iron use. Our data form the basis for a novel mechanism of physiological deficiency that is relevant to human dyserythropoietic anemia and likely other disease states.